The noise impact of airport infrastructure upgrading:A case study of Kuala Lumpur International Airport (KLIA 2) - Bachok, Syahriah (s.n, 2013)
This research focuses on the capturing of sound levels at various points during the construction of Kuala Lumpur International Airport 2, an expansion of the original Kuala Lumpur International Airport. The study utilized two equipment and apparatus namely Noise Dosimeter and Noise Sound Level Meter (SLM) to evaluate the different levels of noise pollution at selected areas within and outside the construction sites. The result of the noise levels are reported accordingly